Challenges and Strategies for Increasing the Popularity of Integrated Islamic Elementary Schools in Jambi Province - Fadlilah Fadlilah; Muhaiminah Jalal; Kiki Fatmawati; Wardatul Janah (Ta'dib, 2025)
The emergence of Integrated Islamic Primary Schools (SDIT) in Indonesia has raised concerns regarding the orientation of Islamic education that is trapped between ideological idealism and market pragmatism. This study aims to describe the challenges and strategies faced by market-oriented SDITs in increasing their popularity. Using a qualitative approach with observation, interview and documentation techniques, this research involved principals, teachers, students and parents. Data analysis followed the Miles and Huberman model, which included collection, presentation, reduction and conclusion drawing. The findings show the main challenges include competition with public schools, curriculum balance, education costs and parents' expectations. Strategies implemented include developing an integrated curriculum, improving the quality of teachers, developing facilities and actively involving parents. This research provides insights into the dynamics of SDIT and offers strategies to overcome challenges in a competitive education market.